2024
DOI: 10.1021/acs.macromol.3c02471
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Crystal Structure and Hydrogen Bonding during Cold Crystallization of Poly(trimethylene 2,5-furandicarboxylate)

Oscar Toledano,
Oscar Gálvez,
Mikel Sanz
et al.

Abstract: Here, we present a detailed description of the in situ isothermal crystallization of poly(trimethylene 2,5-furandicarboxylate)(PTF) as revealed by realtime Fourier transform infrared spectroscopy (FTIR) and grazing incidence wideangle X-ray scattering (GIWAXS). From FTIR experiments, the evolution of hydrogen bonding with crystallization time can be monitored in real time, while from GIWAXS, crystal formation can be followed. Density functional theory (DFT) calculations have been used to simulate FTIR spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…As for the spacer conformation, prior studies suggested that the central C–C bond of PEF adopts a gauche conformation. , Furthermore, an infrared study estimated its trans fraction to be around 10% . DFT calculations using the vdW-DF-cx functional on a single PTF chain suggested that the tggt conformation is the most stable . A DFT study on PBF at the B3LYP/6-311­(d,p) level reported the tgtgt conformation to be the most energetically favorable for the spacer .…”
Section: Resultsmentioning
confidence: 99%
“…As for the spacer conformation, prior studies suggested that the central C–C bond of PEF adopts a gauche conformation. , Furthermore, an infrared study estimated its trans fraction to be around 10% . DFT calculations using the vdW-DF-cx functional on a single PTF chain suggested that the tggt conformation is the most stable . A DFT study on PBF at the B3LYP/6-311­(d,p) level reported the tgtgt conformation to be the most energetically favorable for the spacer .…”
Section: Resultsmentioning
confidence: 99%